A) \[0\]
B) \[1/2\]
C) \[1\]
D) \[3/2\]
Correct Answer: C
Solution :
[c] We have, \[x{{\sin }^{3}}\theta +y{{\cos }^{3}}\theta =\sin \theta \cos \theta \] |
\[(x\sin \theta ){{\sin }^{2}}\theta +(y\cos \theta ){{\cos }^{2}}\theta =\sin \theta \cos \theta \] |
\[x\sin \theta ({{\sin }^{2}}\theta )+(x\sin \theta ){{\cos }^{2}}\theta =\sin \theta \cos \theta \] |
\[x\sin \theta ({{\sin }^{2}}\theta +{{\cos }^{2}}\theta )=\sin \theta \cos \theta \] |
\[x\sin \theta =\sin \theta \cos \theta \,\,\,\,\,\,\Rightarrow \,\,\,\,\,\,\,\,x=\cos \theta \] |
Now,\[x\sin \theta =y\cos \theta \] |
\[\cos \theta \sin \theta =y\cos \theta \] |
\[y=\sin \theta \] |
Hence, \[{{x}^{2}}+{{y}^{2}}={{\cos }^{2}}\theta +{{\sin }^{2}}\theta =1\] |
You need to login to perform this action.
You will be redirected in
3 sec